2020
DOI: 10.3390/ijms21186715
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex-Dependent ADNP Regulation of Muscle Gene Expression Is Correlated with Motor Behavior: Possible Feedback Mechanism with PACAP

Abstract: The activity-dependent neuroprotective protein (ADNP), a double-edged sword, sex-dependently regulates multiple genes and was previously associated with the control of early muscle development and aging. Here we aimed to decipher the involvement of ADNP in versatile muscle gene expression patterns in correlation with motor function throughout life. Using quantitative RT-PCR we showed that Adnp+/− heterozygous deficiency in mice resulted in aberrant gastrocnemius (GC) muscle, tongue and bladder gene expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…A recent study showed that the expression of ADNP enhanced the adaptive ability of malignant peripheral nerve sheath tumors to survive in a malignant environment [16, 35] [16]. The expression of ADNP in bladder was related to age and sex, and is higher in young men [36]. Here we found that the high expression of ADNP leaded to unfavorable prognosis in patients treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study showed that the expression of ADNP enhanced the adaptive ability of malignant peripheral nerve sheath tumors to survive in a malignant environment [16, 35] [16]. The expression of ADNP in bladder was related to age and sex, and is higher in young men [36]. Here we found that the high expression of ADNP leaded to unfavorable prognosis in patients treated with chemotherapy.…”
Section: Discussionsupporting
confidence: 57%
“…These are coupled to NAP enhancement of ADNP interaction with microtubule‐associated protein 1 light chain 3 (LC3) (Merenlender‐Wagner et al, 2015) constituting the autophagosome membrane, indicative of control of fundamental cellular processes. These interactions are further associated with ADNP/NAP control of gene expression central to brain/body functions (Amram et al, 2016; Hacohen‐Kleiman et al, 2018, 2019; Kapitansky, Karmon et al, 2020; Kapitansky, Sragovich et al, 2020; Karmon et al, 2022; Sragovich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More than 400 genes are regulated by ADNP, which are critical for brain formation, organ development, cognition, and motor function (6,(13)(14)(15)(16). In the nucleus, ADNP is a member of a chromatin remodeling complex that is responsible for RNA transcription and splicing (13,(17)(18)(19).…”
mentioning
confidence: 99%